Text-Selection for Teaching Reading to ESL Tertiary Students: A Study on Genre and Content Preferences - Nordin, Razanawati; Lin, Siew Eng (Eskişehir Osmangazi University, 2017)
Most learners studying English language feel that their educators use irrelevant, uninteresting, and culturally unfamiliar reading materials for teaching reading. As a result, most of them struggle to comprehend the English language texts used by the teachers. Therefore, the aim of this research is to investigate the genre and content preferences of ESL tertiary learners in UiTM Kedah, Malaysia. A two-part questionnaire was administered to 132 respondents aged 20 to 23 years old who are presently furthering their undergraduate studies in Accountancy, Administrative Science and Policy Studies, Business Management, Industrial Design, and Information Management. The results of the study show that these ESL tertiary learners prefer texts from the websites and blogs; and their preferred reading contents are dealing with Business Management, watching movies and listening to music. This article offers guidance to ESL teachers to select L2 reading texts based on the students’ preferred genre and content.